1984
DOI: 10.1002/1097-0142(19840701)54:1<34::aid-cncr2820540109>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

The use of scalp hypothermia in the prevention of doxorubicin-induced hair loss

Abstract: A randomized clinical trial was performed to determine the effectiveness of scalp hypothermia in the prevention of hair loss associated with doxorubicin. Twenty‐six patients were randomized to receive scalp hypothermia or chemotherapy alone. Data were analyzed on 25 patients: 12 in the treatment group and 13 in the control group. There was acceptable hair preservation in 75% of the patients who received the scalp hypothermia; only 8% of the patients in the control group had acceptable hair preservation (P = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 6 publications
1
61
0
Order By: Relevance
“…Seven randomized clinical studies have been published which examined the effectiveness of scalp cooling [13,16,21,25,30,34,36]. These studies randomized a total of 233 patients.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Seven randomized clinical studies have been published which examined the effectiveness of scalp cooling [13,16,21,25,30,34,36]. These studies randomized a total of 233 patients.…”
Section: Introductionmentioning
confidence: 69%
“…b The number and percentage of questionnaires on which the statements were answered affirmatively. 8,36]. The recent, more intensive, adjuvant chemotherapy treatments in breast cancer may explain the relatively low success percentage of about 50% in this study.…”
Section: The Effectiveness Of Scalp Coolingmentioning
confidence: 91%
“…However, the cooling techniques in a variety of local application forms have been used to prevent or minimize other conditions like alopecia resulting from chemotherapy. [12][13][14] The hypotheses behind the impact of hypothermia for a localized area have included a variety of proposed factors, ranging from decreased metabolic activity of cells in the local area to decreased blood flow resulting in less drug exposure.…”
Section: Discusssionmentioning
confidence: 99%
“…A comprehensive review, published in 2005, concluded that the majority of findings were positive, with an average success rate prior to and after 1995 of 56% and 73%, respectively (most often based on the World Health Organization [WHO] alopecia grading criteria and less frequently on the need for a wig or a head cover). 60 Six of the seven randomized trials ( N =233) published to date were positive and, of these, five occurred in the 1970s and 1980s, 58, 61-64 whereas only two were more recent. 65, 66 Although the chemotherapy regimens used in these earlier studies differed from more recent studies, other methodological variables including scalp-cooling technique, post-infusion cooling times, duration of chemotherapy infusion, and eligibility criteria make comparisons between studies difficult.…”
Section: Chemotherapy-induced Alopeciamentioning
confidence: 99%